Greenwich Collieries, A Variation In The Art Of Coal Washing By Jigs - C. E. Tackett (Society for Mining, Metallurgy & Exploration, 1977)
The Greenwich Collieries Co. is a subsidiary of the Pennsylvania Mines Corporation, and a wholly owned subsidiary of the PP&L Co. which serves the northeastern portion of Pa. PP&L annually consumes about 11 million tons of coal per year and is the largest consumer of both bituminous and anthracite coal on the eastern seaboard. Development work for Greenwich started in 1969. The coarse coal plant was constructed in 1970, with the raw fines bypassed. This worked very well for our requirements at that time; however, the Greenwich mining plans were extensively changed, longwall mining units were installed and low coal was encountered, resulting in dirtier coal, a finer coal and an ever increasing ash in the shipped product. All this demanded a more efficient ash removal process for the fine coal fraction. In 1971, the Pennsylvania Department of Environmental Resources and the Federal Environmental Protection Agency were pushing for the now stringent sulphur emission limits at our power plants. The Greenwich Mine coal reserves contained large quantities of 3.5 to 4% sulphur along with some low sulphur reserves. It was, therefore, essential that any new plant have the capability of efficient sulphur removal to meet the Pennsylvania Department of Environmental Resources and the Federal Environmental Protection Agency required limits. To meet these limits our design would have to be capable of producing a product of 2.0% sulphur or less.